Eco-Friendly Dyeing and Functional Finishing of Organic Cotton Using Optimized Oolong Tea Stems (Agricultural Waste) Through Response Surface Methodology - Huiya Xu; Chen Yang; Ha-young Song (Molecules)
As people attempt to elude the environmental issues associated with synthetic dyes, interest in natural dyes has recently increased significantly. Oolong tea stems act as a common agricultural waste yet offer advantages like high production, low cost, and a stable supply. The objectives of this research are to investigate the potential utilization of oolong tea waste, specifically tea stems, as a natural dye source for the development of organic cotton fabrics with added health benefits. In this study, using the Kubelka–Munk (K/S) value as an indicator, the dyeing process was refined through response surface methodology (RSM) by investigating the pH of the dye solution, temperature, and duration. Accordingly, it was demonstrated that the optimal effect was achieved at a pH value of 7.9, a duration of 80 min, and a temperature of 90 °C. Furthermore, under these conditions, the color fastness and functional performance of dyed organic cotton were compared with and without chitosan as a mordant. The results showed that the organic cotton dyed with oolong tea stem extract not only had a good color fastness grade but also presented excellent antibacterial properties, ultraviolet protection properties, and oxidation resistance. Especially with the assistance of chitosan, the dyed fabric achieved excellent performance above grade 4 in all color fastness test items; moreover, its antibacterial activity against Staphylococcus aureus reached more than 90%, the ultraviolet protection coefficient reached 25.3, and the antioxidant activity exceeded 90%. Consequently, considering environmental concerns, natural dyes extracted from discarded oolong tea stems are promising substitutes for synthetic dyes in the textile sector.